PERLUASAN KESEMPATAN KERJA BAGI MASYARAKAT PESISIR - Handayani, Sri Wahyu (Proceeding SENDI_U, 2015)
Embodiment maritime shaft in economic development based on the citizenâs prosperity in Indonesia whichhas an area of ocean 80% of the land area is a aspired thing. This is one of effort welfare distributions wich is inline with Indonesian manpower development based on Pancasila and UUD 1945 namely through implementationof manpower development based on the principle of integrity through coordination functional cross-sectoral andregional centers as listed in Law No 13 of 2003 about Employment. The success of the maritime developmentmust be felt by coastal communities in the vicinity who mostly work as fishermen and have low education, so itneeds to be a concern efforts to improve the standard of living in coastal areas and overcoming the problem ofunemployment. Therefore, coastal communities will not have limited mind about land because of the publicationRegulation of The Minister of Marine and Fisheries No 1 of 2015 and No2 of 2015 actually two rules are amandate from Law No 31 of 2004. The role of both central and local government are required to handle thisexpansion of employment opportunities, both within and outside the employment relationship especially infacing the challenges of globalization.The method used to solve this problem is the legal research, which meansthat it is intended to examine the rules and principles of law, whereas the approach method is used byemphasizing on normative juridical approach. Based on normative juridical research method, then some stepswill be applied in this study include: First,inventory of legislation relating to the expansion of employmentopportunities;Second, the inventory of the problems that appear, in the implementation on the expansion of theemployment opportunities. The aim of this research is to examine analytical studies on legislation andoperational regulations governing about the expansion of employment opportunities which can be appliedespecially in the coastal areas, so the researcher obtains a conclusion regarding the implementation model on theexpansion of employment opportunities in coastal areas.Keywords :the expansion of employment opportunities, employment relations, maritime shaft